Fabrication and tribological characterization of deformation-resistant nano-textured surfaces produced by two-photon lithography and atomic layer deposition. (April 2019) - Steck, Jason G.; Afshar-Mohajer, Mahyar; Sun, Qian; Meng, Xiangbo; Zou, Min
Abstract: In this study, we demonstrated a novel strategy for fabricating deformation-resistant nano-textured surfaces. Ordered arrays of IP-DIP photoresist nanodots of various diameters were first fabricated using two-photon lithography. IP-DIP/Al2 O3 core-shell nanostructures (CSNs) were then formed by conformally coating the nanodots with Al2 O3 of different thicknesses via atomic layer deposition (ALD). The CSNs showed 85% lower coefficients of friction than the bare IP-DIP nanodots and exhibited minimal nanostructure deformation at contact pressures greater than 20 GPa. The IP-DIP/Al2 O3 CSNs also have lower adhesion forces than the bare IP-DIP nanodots. The excellent deformation resistance and superior tribological properties of these CSNs demonstrate that the combination of two-photon lithography and ALD is a very promising solution to tribological issues in miniaturized systems. Graphical abstract: Highlights: IP-DIP nanotextures were printed on silica substrate using two-photon lithography. Hard amorphous Al2 O3 shells were deposited on the nanotextured surfaces by ALD. The printed IP-DIP nanotextures have 80% greater COFs than bare silica substrate. IP-DIP/Al2 O3 core-shell nanostructures (CSNs) show no deformation below 2000 μN. Only minimal CSN deformation occurred at an estimated contact pressure >20 GPa.